UPAYA PEMERINTAH DALAM MENGATASI MASALAH PELAKSANAAN PROGRAM SPP DI JORONG PADANG TUJUH KANAGARIAN AUA KUNIANG KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - Dayu, Resti Deliyasmie (Pendidikan Sosiologi, 2014)
Womens Savings and Loans (SPP) is a womens savings and loans throughout the loan program and the nature of the UPK (Project Management Unit) which is used by the community to fund economic activities by community groups. However, in the implementation of womens credit program in Padang Seven Jorong there are problems in the implementation, so that the formulation of the problem in this study is what factors are causing the problem in the implementation of the SPP program in Padang Jorong Seven and how the governments efforts to address the problems in the implementation of the SPP program Seven Jorong Padang. The purpose of this study was to describe the factors causing problems in the implementation of the SPP program Jorong Padang Seven and describe the governments efforts to address the problems in the implementation of the SPP program Jorong Nagari Padang Seven Aua Kuniang Pasaman District of West Pasaman. The theory used in this study is the theory of action (action theory) proposed by Talcott Parsons. The method in this study using qualitative methods. The technique used for data collection is the technique of observation, interview and documentation. The information in this study are set intentionally (purposive sampling), the number of informants in whole is 20 persons, 16 members of the group Wine XI, 4 board members and cadres UPK. Based on the results of studies that have revealed that there are three factors that contributed to the problems in the implementation of the SPP program Jorong Padang Seven are: 1) late payment, 2) the utilization of funds is not in accordance with uaha productive, 3) the SPP funds are not correspond with the objectives has been established, while the shape of the governments efforts to address the problems in the implementation of the SPP program Jorong Padang Seven are: 1) to form a team for the handling of problems from the field, 2) to deliberate between groups and the attendant fees, 3) to sanction the troubled group